Sustainable remediation of Cd-contaminated farmland through the rotation of rapeseed–rice varieties with different Cd accumulation potentials - Liang Wang; Qiqing Liu; Jingyi Fu; Yuxuan Xiao; Jun Yang; Xiaoyong Liao (Ecotoxicology and Environmental Safety)
In response to the safety risks posed by cadmium (Cd)-contaminated rice fields worldwide, a suitable production-and-restoration strategy is required for actual agricultural practices. To investigate the remediation effects of different accumulation varieties in rapeseed−rice cropping systems and their influence on Cd migration and transportation, field experiments were conducted based on different planting combinations (FWHR, conventional rice variety (HR) monoculture under fallow; FWLR, low Cd-accumulating rice variety (LR) monoculture under fallow; LOLR, LO (low Cd-accumulating rapeseed variety)-LR rotation; LOHR, LO-HR rotation; HOLR, HO (high Cd-accumulating rapeseed variety)-LR rotation; HOHR, HO-HR rotation). The study found that a rapeseed and rice rotation with appropriate varieties could reduce the rice grain Cd content, increase rice yield, and remove soil Cd without affecting agricultural production efficiency. Compared to the fallow-conventional rice pattern, various rapeseed−rice rotations reduced the Cd content of rice grains by 15 %–38 %, and significantly increased the available potassium (Ava-K) in the subsequent rice soil by 29.6–56.4 mg/kg. The total economic benefits increased by $500–$1800 per hectare. A high accumulation variety of rapeseed and low accumulation variety of rice produced the most effective reduction in Cd levels, with a reduction rate of 38 % in brown rice and an annual removal rate of 24.42 g/hm2. This combination also resulted in a 29 % increase in rice yield compared to the fallow-low accumulation variety rice pattern. Structural equation modeling revealed that with the combined action of crop rotation and variety selection the crop rotation directly reduced the soil available Cd or had an indirect effect by weakening the root-zone acidification effect and increasing soil Ava-P. The rotation of rapeseed and rice with carefully selected matching varieties is a feasible solution for the safe production and pollution remediation of Cd-contaminated paddy fields.